Linear Social Interactions Models - Blume, Lawrence E.; Brock, William A.; Durlauf, Steven N.; Jayaraman, Rajshri (Journal of Political Economy, 2015)
This paper provides a systematic analysis of identification in linear social interactions models. This is a theoretical and econometric exercise as the analysis is linked to a rigorously delineated model of interdependent decisions. We develop an incomplete information game for individual choice under social influences that nests standard models as special cases. We consider identification of both endogenous and contextual social effects under alternative assumptions regarding an analyst’s a priori knowledge of social structure or access to individual-level or aggregate data. Finally, we discuss potential ramifications for identification of endogenous formation of social structure.